2014
DOI: 10.1016/j.schres.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Brain circuit dysfunction in a distinct subset of chronic psychotic patients

Abstract: Objective To identify the mechanism of unexplained hyponatremia and primary polydipsia in schizophrenia and its relationship to the underlying psychiatric illness. Methods Briefly review previous studies that led to the conclusion the hyponatremia reflects altered hippocampal inhibition of peripheral neuroendocrine secretion. In greater detail, present the evidence supporting the hypothesis that circuit dysfunction associated with the hyponatremia and the polydipsia contributes to the underlying mental disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 136 publications
(169 reference statements)
1
14
0
2
Order By: Relevance
“…The findings may partially replicate other morphometric research findings, where a two-sided decrease in the volume of the front part of the hippocampi in comparison with schizophrenics with no polydipsia [26,28,29] was found in patients with schizophrenia, polydipsia and transient hyponatremia. In those studies, the atrophy was two-sided and related to the front parts of the hippocampi, i.e.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The findings may partially replicate other morphometric research findings, where a two-sided decrease in the volume of the front part of the hippocampi in comparison with schizophrenics with no polydipsia [26,28,29] was found in patients with schizophrenia, polydipsia and transient hyponatremia. In those studies, the atrophy was two-sided and related to the front parts of the hippocampi, i.e.…”
supporting
confidence: 87%
“…Uzyskane wyniki mogą stanowić częściowe powtó-rzenie wyników innych badań morfometrycznych, w któ-rych u chorych ze schizofrenią, polidypsją i przemijającą hiponatremią wykazano obustronne zmniejszenie obję-tości przedniej części hipokampów w porównaniu z chorymi na schizofrenię bez polidypsji [26,28,29]. W tych pracach zanik był obustronny i dotyczył przednich czę-ści hipokampów, tzn.…”
unclassified
“…Authors of subsequent studies emphasize that disturbances in the regulation of the oxytocynergic system are associated with the pathophysiology of psychotic disorders [47,56]. It was found that patients diagnosed with schizophrenia had reduced blood plasma oxytocin concentration.This is particularly evident in patients with the PIP-syndrome: psychosis-intermittent hyponatremiapolydipsia) [56,57].…”
Section: The Role Of Oxytocin In the Pathophysiology Of Schizophreniamentioning
confidence: 98%
“…Autorzy kolejnych badań podkreślają, iż zaburzenia w regulacji systemu oksytocynergicznego wiążą się z patofizjologią zaburzeń psychotycznych [47,56]. Stwierdzono, iż pacjenci z rozpoznaniem schizofrenii mają obniżone stężenie oksytocyny w osoczu krwi.Jest to szczególnie widoczne u pacjentów z towarzyszącym zespołem psychoza-hiponatremia-polidypsja(PIP-syndrome: psychosis-intermittenthyponatremia-polydipsia) [56,57].…”
Section: Rola Oksytocyny W Patofizjologii Schizofrenii -Oksytocynowy unclassified
“…Fluid satiation is a key homeostatic signal which limits the amount of fluid ingested and prevents the potentially lethal consequences of overhydration, such as severe hyponatremia and cerebral edema, which can occur in patients with psychogenic polydipsia (Goldman ). Tight control of fluid homeostasis is vital for maintaining cell size which is required for proper cell functioning; and for maintaining stable blood volume and pressure, which are necessary for transporting essential nutrients and oxygen around the body (Leib et al.…”
Section: Introductionmentioning
confidence: 99%